Do Belonging and Social Exclusion at School Affect Structural Brain Development During Adolescence?. Issue 6 (22nd June 2021) - Raufelder, Diana; Neumann, Nicola; Domin, Martin; Lorenz, Robert C.; Gleich, Tobias; Golde, Sabrina; Romund, Lydia; Beck, Anne; Hoferichter, Frances
Abstract : Students' sense of belonging presents an essential resource for academic and health outcomes, whereas social exclusion at school negatively impacts students' well‐being and academic performance. Aiming to understand how feelings of school‐related belonging and exclusion shape the structural brain development, this study applied longitudinal questionnaire‐based data and MRI data from 71 adolescent students (37 females, M age at t1 = 15.0; t2 = 16.1 years). All were white participants from Germany. Voxel‐based morphometry revealed only an association of social exclusion (and not of belonging) and gray matter volume in the left anterior insula: From t1 to t2, there was less gray matter decrease, the more social exclusion students perceived. School‐related social exclusion and disturbed neurodevelopment are thus significantly associated.